An Eye on Movement Disorders. Issue 8 (10th August 2021) - Wilson, Duncan; Hallett, Mark; Anderson, Tim
ABSTRACT: Eye disorders spanning a range of ocular tissue are common in patients with movement disorders. Highlighting these ocular manifestations will benefit patients and may even aid in diagnosis. In this educational review we outline the anatomy and function of the ocular tissues with a focus on the tissues most affected in movement disorders. We review the movement disorders associated with ocular pathology and where possible explore the underlying cellular basis thought to be driving the pathology and provide a brief overview of ophthalmic investigations available to the neurologist. This review does not cover intracranial primary visual pathways, higher visual function, or the ocular motor system.